Russia-Ukraine War: Question on Efficiency of United Nations Organization - Gautam, Mahendra (Interdisciplinary Journal of Management and Social Sciences, 2023)
This article analyses the role of the United Nations Organization that has become subdued in the Russia- Ukraine War. It has forced World Leaders to pose questions about its efficiency in preventing the world from a looming Global War. Russia and Ukraine are the immediate neighbors sharing socio-cultural dynamics adjacently. In the former USSR regime in Ukraine, people of Russian origin are residing with long-standing ancestral history. However, the recent tension between them is created by their distinct strategic interest in national security. That has forced them to go to war in no time. The event has questioned the relevance and efficiency of global bodies like the UN in preventing war. In the aforementioned war, the United Nations has failed in war prevention. More than that UN’s objective of creating peace and sustainability is seen as challenged by emerging bilateral wars in different geographies of the world in different historical contexts. Rather than cooperation the entire world is stepping toward hatred and suspicion. No region is free from conflict of different nature. The battle of creeds in Africa, Religious conflict in the Middle East, different bilateral wars like the India-Pakistan war, Iraq- America war, Israel- Palestine war, and at present Russia-Ukraine war have emerged as challenges to the pragmatic approach of a global institution, the UN in the prevention of war. Regarding this, the present research mainly focuses on the role of the United Nations in the ongoing Russia-Ukraine war to analyze the relevance and effectiveness of the United Nations as the war-preventing global organization.